2015
DOI: 10.1080/07373937.2015.1036282
|View full text |Cite
|
Sign up to set email alerts
|

Wet Oxidation as an Advanced and Sustainable Technology for Sludge Treatment and Management: Results from Research Activities and Industrial-Scale Experiences

Abstract: In this article, the effectiveness of an advanced sludge treatment technology (Wet Oxidation, WO) is presented by analyzing experimental studies at the lab scale and data collected during years of industrial-scale activities. The data showed good performances of WO on COD and VSS removal efficiencies-about 65-70% and 95-98%, respectively-and the effect of operating parameters (i.e., temperature and reaction time) on process efficiencies was highlighted. The energy balance of the WO systems indicated that about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…This gives an upper range value of energy consumption for wastewater treatment by membrane processes. For the WAO process, an energetic study of an industrial WAO plant process working under the same range of operating conditions than the one of this paper was evaluated . The energy inputs in WAO are feed chemical energy (coming from the organic pollutants), thermal energy (to reach the high temperature in the reactor), and electric energy (for pressurization, mixing, and circulation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This gives an upper range value of energy consumption for wastewater treatment by membrane processes. For the WAO process, an energetic study of an industrial WAO plant process working under the same range of operating conditions than the one of this paper was evaluated . The energy inputs in WAO are feed chemical energy (coming from the organic pollutants), thermal energy (to reach the high temperature in the reactor), and electric energy (for pressurization, mixing, and circulation).…”
Section: Resultsmentioning
confidence: 99%
“…As examples, a 91% COD removal rate was obtained for wastewater from the textile industry, and an 86% COD removal rate was obtained for wastewater polluted by surfactants and mineral oils . The major drawback of this process is the operating costs, mainly coming from energy consumption for pumping, pressurizing, mixing, and heating even with auto‐thermal operation . This drawback becomes crippling if the concentration of organic pollutants is really low .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in the past, WO did not meet the favors of the practitioners because it was considered too complex, expensive and energy demanding for sludge treatment. Actually, no severe conditions are requested for sludge treatment by means of WO process for achieving even high volatile suspended solids (VSS) removal efficiency (in the magnitude of 90%, as reported in Slavik et al, 2014); for typical WO working conditions and performances, the reader can refer to Bhargava et al (2006), Bertanza et al (2014 a), Hii et al (2014) and Slavik et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the technicians are motivated to improve or find alternative remediation technologies finalized to close the remediation cycle, and give a new life to waste.A technology that can be useful in reaching the aforementioned targets is the wet oxidation (WO) process, which is reliable and effective in the treatment of a wide spectrum of organic aqueous waste, even toxic waste, produced by various branches of industrial activity [8,9], and sewage sludge [10].Typical treatment conditions for sludge and hazardous wastes reported in the literature are as follows: 200-325 • C for temperature; 5000-17,500 kPa for pressure; and 15-120 min for the reaction time. The preferred COD load ranges from 10-80 kg·m −3 .One of the biggest advantages related to the WO process is that decontamination is obtained with low polluting output gases, composed mainly of CO 2 , water steam, and oxygen, without hazardous by-products and low organic content in the final residue [8,11,12]. In addition, the WO effluent can be conveniently treated in a conventional wastewater treatment plant because of its high biodegradability, and, in some cases, it could also be used as a carbon source for the denitrification process, and as a substrate for the production of biopolymers [12].…”
mentioning
confidence: 99%
“…The preferred COD load ranges from 10-80 kg·m −3 .One of the biggest advantages related to the WO process is that decontamination is obtained with low polluting output gases, composed mainly of CO 2 , water steam, and oxygen, without hazardous by-products and low organic content in the final residue [8,11,12]. In addition, the WO effluent can be conveniently treated in a conventional wastewater treatment plant because of its high biodegradability, and, in some cases, it could also be used as a carbon source for the denitrification process, and as a substrate for the production of biopolymers [12]. Moreover, other researchers have also demonstrated that WO effluent represents an interesting energy vector; in fact, if it is treated by anaerobic digestion, biogas can be produced, and electric and thermal energy could be recovered [13].Today, about 200 plants are in operation around the world (two of them in Italy), mostly to treat waste streams from petrochemical, chemical, and pharmaceutical industries, as well as residual sludge from urban wastewater treatment [12].…”
mentioning
confidence: 99%